Oxygen insecurity and mortality in resource‐constrained healthcare facilities in rural Kenya. Issue 4 (10th February 2020) - Otiangala, Dickson; Agai, Nicholas O.; Olayo, Bernard; Adudans, Steve; Ng, Chin Hei; Calderon, Ryan; Forgie, Ella; Bachman, Christine; Lieberman, Daniel; Bell, David; Hawkes, Michael; Somoskovi, Akos
Abstract: Introduction: Pneumonia is the leading cause of death globally in children. Supplemental oxygen reduces mortality but is not available in many low‐resource settings. Inadequate power supply to drive oxygen concentrators is a major contributor to this failure. The objectives of our study were to (a) assess the availability of therapeutic oxygen; (b) evaluate the reliability of the electrical supply; and (c) investigate the effects of suboptimal oxygen delivery on patient outcomes in selected healthcare facilities in rural Kenya. Materials and Methods: A cross‐sectional descriptive study on oxygen availability and descriptive case series of Kenyan children and youth hospitalized with hypoxemia. Results: Two of 11 facilities had no oxygen equipment and nine facilities had at least one concentrator or cylinder. Facilities had a median of seven power interruptions per week (range: 2‐147). The median duration of the power outage was 17 minutes and the longest was more than 6 days. The median proportion of time without power was out 7% (range: 1%‐58%). Fifty‐seven patients hospitalized with hypoxemia (median oxygen saturation 85% [interquartile range IQR: 82‐87]) were included in our case series. Patients received supplemental oxygen for a median duration of 4.6 hours (IQR: 3.0‐7.8). Eighteen patients (32%) faced an oxygen interruption of the median duration of 11 minutes (IQR: 9‐20). A back‐up cylinder was used in 5/18 (28%) cases. The case fatality rate was 11/57 (19%). Conclusion: Mortality due to hypoxemia remains unacceptably high in low‐resource healthcare facilities and may be associated with oxygen insecurity, related to lack of equipment and/or reliable power.